ANALYSIS OF FINANCIAL PERFORMANCE IN THE HOME INDUSTRY OF KERUPUK TEMPE IN MATANG MUNYE, SYAMTALIRA ARON SUB-DISTRICT - Nur Azizah; Mariyana BR Manik; Sumarni; M. siddiq; Rico Nur Ilham (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Tempe crackers are a type of puli/karak crackers mixed with soybean crackers. These crackers are a new product from existing types of crackers, such as prawn crackers, onion crackers, karak and cassava crackers. Products from agriculture such as soybean production can be commodity or very expensive quality such as tempeh crackers, besides being able to meet the needs of the community it also opens business opportunities for the community to do entrepreneurship. Assessment of financial performance is one way that can be done by the management in seeing the achievement of profits earned by a company. This financial performance can be measured by analyzing and evaluating the company's financial statements by looking at the company's financial position in a certain period so that it can be seen the achievements of a company.